Peran Kepercayaan Konsumen dalam Memediasi Pengaruh Layanan Telefarmasi terhadap Keputusan Pembelian Kembali - Muh. Ilham Safar Bumulo; Yulinda L. Ismail; Citra Aditya Kusuma (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
The purpose of this study is to examine how telepharmacy services affect repurchase intention, how telepharmacy services affect customer trust, and how consumer trust functions as a mediator at Pinan Farma Pharmacy. This study uses a causal associative design and a quantitative methodology. Purposive sampling was utilized to pick a sample of 84 respondents from the population of 507 consumers who used telepharmacy services between June and November of 2025. Structural Equation Modeling based on Partial Least Squares (SEM-PLS) using SmartPLS 4 was used to examine the data. The findings show that consumer trust and repurchase intention are positively and significantly impacted by telepharmacy services. Furthermore, repurchase intention is positively and significantly impacted by customer trust, which also partially mediates the association between telepharmacy services and repurchase intention. These results imply that raising the standard of telepharmacy service, particularly in patient education and pharmacist competence, is essential to strengthen consumer trust and encourage repurchase intention.